(Invited) Highly Stable Self-Aligned Top-Gate Indium Gallium Zinc Oxide Thin-Film Transistors for High-Resolution OLED TV and Mobile Displays. (8th September 2020) - Kim, Jung Bae; Tsai, Yun-chu (Pipi); Lim, Rodney; Wang, Zhiyuan; Hao, Mei; Wang, Sheng-Wen (Gordon); Park, Jung Woo; Zhao, Lai; Bender, Marcus; Yim, Dong Kil; Choi, Soo Young
Abstract : Highly stable self-aligned coplanar top-gate InGaZnO (IGZO) thin-film transistors (TFTs) with excellent threshold voltage (Vth) uniformity are developed by optimizing gate insulator film properties and controlling oxygen/hydrogen diffusion into IGZO channel. The TFTs do not show notable negative Vth shift and Vth non-uniformity from channel length 10 µm down to 3 µm. The TFTs also show no notable Vth shift during a humidity test in a chamber at 85°C/85% after deposition of passivation layers or even after 1-µm-thick thin-film encapsulation (TFE) SiNx layer on the top of the passivation layer due to the high quality/low hydrogen 2 nd SiNx passivation layer deposited on the top of 1 st SiOx passivation layer.